Pemodelan Smartapps Sistem Terintegrasi Metode System Development Life Cycle untuk Aplikasi Layanan Administrasi di UNIKOM - Kurniawan, Bobi; Herdiana, Budi; Alviana, Sopian (Majalah Ilmiah Teknologi Elektro, 2019)
Smartapps is an integrated one-door service information system that is intended to provide information related to the filing of RFID cards for employees and lecturers, submission of vehicle number plate data, checking and printing of employee attendance reports, and reports on the distribution of suits and books for new students. The development of this application model refers to the problems that arise that are all administrative processes so far still using manual systems that have an impact on the efficiency of service time to be longer. Therefore the goal achieved from this research is that the system works well and is able to facilitate the management of integrated data so that it can be accessed quickly by referring to the results of system testing which shows the user response rate reaches 89.87% of the total 40 respondents. Keywords: smartapps, information system, presence, RFID, database